2020
DOI: 10.3389/fmars.2020.00647
|View full text |Cite
|
Sign up to set email alerts
|

Movements of Juvenile Green Turtles (Chelonia mydas) in the Nearshore Waters of the Northwestern Gulf of Mexico

Abstract: Satellite telemetry is a valuable tool for examining long-term, large scale movements of highly migratory species. Tracking data can be used by resource managers to protect habitat and ensure recovery of threatened and endangered species. Few tracking studies have focused on habitat use patterns of juvenile, neritic stage turtles. Satellite tracking surveys were conducted to assess juvenile green turtle movements in the northwestern Gulf of Mexico during 2006-2010. Fifteen turtles were equipped with platform t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
1
11
1
2
Order By: Relevance
“…Los datos de temperatura oscilaron de 24.8 a 30.3 °C (promedio ± DE= 28.4 ± 2.66) (Tabla 1). Las tortugas marinas suelen encontrarse activas a diversas temperaturas, con distintos umbrales a favor de la zona geográfica en la cual residan (Mendonça, 1983;Hazel et al, 2009;Lamont et al, 2015;Álvarez-Varas et al, 2017;Metz et al, 2020); no obstante, registros desmesurados, durante lapsos prolongados, alteran su comportamiento e incluso conllevan a la muerte (Bitón-Porsmoguer, 2009).…”
Section: Profundidad (M)unclassified
See 1 more Smart Citation
“…Los datos de temperatura oscilaron de 24.8 a 30.3 °C (promedio ± DE= 28.4 ± 2.66) (Tabla 1). Las tortugas marinas suelen encontrarse activas a diversas temperaturas, con distintos umbrales a favor de la zona geográfica en la cual residan (Mendonça, 1983;Hazel et al, 2009;Lamont et al, 2015;Álvarez-Varas et al, 2017;Metz et al, 2020); no obstante, registros desmesurados, durante lapsos prolongados, alteran su comportamiento e incluso conllevan a la muerte (Bitón-Porsmoguer, 2009).…”
Section: Profundidad (M)unclassified
“…Las tortugas marinas mitigan el efecto de la temperatura mediante acciones alternativas tales como el adormecimiento temporal, disminución de las actividades (Contreras-Salazar, 2008), hábitos migratorios (González-Carman et al, 2012;Metz et al, 2020), cambio en la distribución dentro de la columna del agua (Lamont et al, 2015), entre otras. La sensibilidad de los organismos a dicho parámetro varía en razón de la edad (Sevilla, 1977) estado de salud o tamaño de los individuos (Márquez, 1996).…”
Section: Profundidad (M)unclassified
“…Juvenile turtles throughout the world have been shown to exhibit multi-year fidelity to foraging areas (González Carman et al, 2016;Metz et al, 2020;Siegwalt et al, 2020), which further highlights their importance in the conservation and recovery of these species. In Australia, green turtles and loggerheads remained in foraging habitats for 17 and 23 years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, green turtles and loggerheads remained in foraging habitats for 17 and 23 years, respectively. The size of these home ranges varies greatly among species and studies, most likely a factor of study methods used, duration of tracking periods, and environmental conditions (Metz et al, 2020). For example, mean size of core use areas for green turtles in Northeast Florida was 4.4 ± 1.3 km 2 (Wildermann et al, 2019) while along the Texas coast, the mean size for green turtles in summer was much larger (125.4 ± 47.5 km 2 ) and when examining only winter core use areas, the mean size in Texas was even greater (543.7 ± 230.6 km 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research using telemetry to track juvenile green turtles in the Gulf of Mexico has revealed that they generally use small core use areas in nearshore foraging habitats at this life stage Lamont et al, 2015;Wildermann et al, 2019), although seasonal differences in foraging ranges have been reported (Metz et al, 2020). Satellite tracking data for adult green turtles nesting on United States Gulf of Mexico beaches are currently limited to studies at Dry Tortugas, where post-nesting movements have been documented both within the park and the surrounding areas of the Florida Keys (Hart et al, 2013).…”
Section: Introductionmentioning
confidence: 99%